Expression and Regulation of Hypoxia-Inducible Factor Signalling in Acute Lung Inflammation - Nikolaos S. Lotsios; Chrysi Keskinidou; Sotirios P. Karagiannis; Kostas A. Papavassiliou; Athanasios G. Papavassiliou; Anastasia Kotanidou; Ioanna Dimopoulou; Stylianos E. Orfanos; Alice G. Vassiliou (Cells)
Hypoxia-inducible factors (HIFs) are central regulators of gene expression in response to oxygen deprivation, a common feature in critical illnesses. The significant burden that critical illnesses place on global healthcare systems highlights the need for a deeper understanding of underlying mechanisms and the development of innovative treatment strategies. Among critical illnesses, impaired lung function is frequently linked to hypoxic conditions. This review focuses on the expression and regulation of HIF signalling in experimental models of acute lung injury (ALI) and clinical studies in critically ill patients with acute respiratory distress syndrome (ARDS). We explore the potential dual role of HIF signalling in acute lung inflammation. Furthermore, its role in key biological processes and its potential prognostic significance in clinical scenarios are discussed. Finally, we explore recent pharmacological advancements targeting HIF signalling, which have emerged as promising alternatives to existing therapeutic approaches, potentially enabling more effective management strategies.